Is intuitive eating linked to waist circumference and the waist-to-height ratio, both of which are risk factors for cardiometabolic disease? - Yaşar Fırat, Yağmur; Cicek, Betul (Progress in Nutrition, 2023)
Background and aim: Intuitive eating is related to lower BMI, blood triglyceride levels and cardiovascular risk and also it decreases the symptomatology of eating disorders and improves psychological health criteria. In this study, it was aimed to examine the relationship between the intuitive eating, waist circumference and waist-to-height ratio of college students.Methods: This study was conducted on 1708 students. A questionnaire was used for socio-demographic characteristics, and nutritional habits. the Intuitive Eating Scale-2. Anthropometric measurements were measured by researcher and body mass index and waist-to-height ratio were calculated.Results: Total intuitive eating scores and eating for physiological rather than emotional reasons subscale scores were significantly higher in the normal waist circumference and the risk groups than in the high-risk group. Total intuitive eating scores and eating for physiological rather than emotional reasons subscale scores were significantly higher in the non-increased risk and increased risk groups, compared to very-high risk group.Conclusions: As the waist circumference and waist-to-height ratio values approach the normal limits, the intuitive eating score also increases. Waist circumference and waist-to-height ratio may be considered as indicators of intuitive eating.